2014
DOI: 10.1155/2014/791045
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs in Plasma of Hepatitis B e Antigen Positive Children Reveal Liver-Specific Target Genes

Abstract: Background and Aim. Hepatitis B e antigen positive (HBeAg-positive) children are at high risk of severe complications such as hepatocellular carcinoma and cirrhosis. Liver damage is caused by the host immune response to infected hepatocytes, and we hypothesise that specific microRNAs play a role in this complex interaction between virus and host. The study aimed to identify microRNAs with aberrant plasma expressions in HBeAg-positive children and with liver-specific target genes. Methods. By revisiting our pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…There is supporting evidence that hepatic stellate cells (HSCs) and macrophages can influence the differentiation of liver progenitor cells into reactive biliary cells and bile ducts by the Notch pathway, therefore suggesting a potential role of miR‐34a in the manifestation of CFLD. A potential role of miR‐365 has been implicated in pediatric CLD, including biliary atresia, and increased levels of circulating miR‐365a‐3p have been found in the plasma of children with hepatitis B, suggesting its potential as a biomarker for disease progression . However, further mechanistic studies are required to fully elucidate the role of miR‐34a‐5p and miR‐365a‐3p in the pathogenesis of these pediatric liver diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is supporting evidence that hepatic stellate cells (HSCs) and macrophages can influence the differentiation of liver progenitor cells into reactive biliary cells and bile ducts by the Notch pathway, therefore suggesting a potential role of miR‐34a in the manifestation of CFLD. A potential role of miR‐365 has been implicated in pediatric CLD, including biliary atresia, and increased levels of circulating miR‐365a‐3p have been found in the plasma of children with hepatitis B, suggesting its potential as a biomarker for disease progression . However, further mechanistic studies are required to fully elucidate the role of miR‐34a‐5p and miR‐365a‐3p in the pathogenesis of these pediatric liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A potential role of miR-365 has been implicated in pediatric CLD, including biliary atresia, (44) and increased levels of circulating miR-365a-3p have been found in the plasma of children with hepatitis B, suggesting its potential as a biomarker for disease progression. (33,45) However, further mechanistic studies are required to fully elucidate the role of miR-34a-5p and miR-365a-3p in the pathogenesis of these pediatric liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Winther et al identified liver specific target genes in plasma of HBeAg+ children (Table 3) [149]. Using the raw data from the original study [147], plasma miRNA expression was re-analyzed from HBeAg+, HBeAg− and the healthy control groups.…”
Section: Circulatory Mirnas As Biomarkers In Paediatric Liver Diseasementioning
confidence: 99%
“…Current knowledge on the pathogenesis at the molecular level is, however, limited [ 13 ]. We previously identified a panel of differentially expressed microRNAs in plasma from children with CHB [ 14 ] and furthermore showed that a number of the identified microRNAs had liver-specific target genes [ 15 ]. Liver tissue samples are unavailable as the majority of children with CHB are asymptomatic.…”
Section: Introductionmentioning
confidence: 99%